Determining a Feasible Working Condition for Hydrostatic Spindle Bearings of the External Circular Grinding Machine 3K12 - Bui, Tuan-Anh; Nguyen, Manh-Toan; Pham, Van-Hung (Old Journal, 2020)
In a hydrostatic spindle of machine tools, the bearing structure parameters, lubrication characteristics and working conditions are factors affecting the spindle stiffness and the machining quality. Besides some known geometrical parameters and oil viscosity, other factors such as lubricant pressure and loading capacity need to be determined to find a feasible working condition for a machine tool. This study presents the experimental results of the effect of pump pressures and loads on the stiffness of the spindle integrated a new designed and fabricated hydrostatic bearing. The experiment results show that, with a known oil viscosity of 0.002 PaS, a pump pressure of 5 MPa and a load in a range 500 – 1000 N are the most feasible working condition of the medium–sized external circular grinding machine 3K12.